La evaluación y revisión del criterio de ciudadanía y su distinción de otros conceptos similares en la legislación iraní - Abbas Zera’at; Meysam Nematollahi (Universidad Hemisferios, 2017)
Citizenship is one of the concepts discussed in most fields of humanities. Each field has studied it within a context regarding its perspective. The criterion of citizenship has been neglected in most of these studies and has received less attention. Who are the subjects of this word? This argument is necessary because words have their own effects and cases in the law; therefore, it is necessary to determine the subject before the other rights and duties are considered. Similarly, the present research is an attempt to find out what people are subject to citizenship. By considering the existing rules of the law, it can be seen that issues such as nationality and residence are older than “citizenship”. However, none of these issues can be a criterion for citizenship. Even the subject of human legal documents cannot be dealt with as a criterion of citizenship because the acceptance of each criterion has some challenges. What is certain is that being a citizen is itself a factor for citizenship and should be considered as a condition for citizenship according to its components.